2017
DOI: 10.1039/c7cp01993a
|View full text |Cite
|
Sign up to set email alerts
|

Cation distribution: a key to ascertain the magnetic interactions in a cobalt substituted Mg–Mn nanoferrite matrix

Abstract: The effect of Co substitution into nanocrystalline Mg-Mn ferrite synthesized by a solution combustion technique has been studied. The cation distribution has been inferred from X-ray diffraction, the magnetization technique, and Mössbauer spectroscopy. The X-ray analysis and cation distribution data have been used to investigate the detailed structural parameters such as hopping lengths, ionic radii of tetrahedral and octahedral sites, oxygen positional parameter, site bond as well as edge lengths, bond length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…The cation distribution in the tetrahedral and octahedral sites in partially inverse spinel ferrites can be deduced on the basis of both Rietveld refinement of XRD data and the intensity ratio in the Mössbauer spectra of the sextets due to Fe 3+ cations in the tetrahedral and octahedral sites. Taking into account that combined XRD and Mössbauer spectral studies partially inverse spinel ferrites have concluded that the cation distribution obtained from the X-ray intensity data matches very well with the cation distribution estimated from Mössbauer data, [49][50][51][52] and that the diffraction profile analysis with the Rietveld method allows simultaneously getting the relevant information of the material microstructure, it was selected the use of X ray diffraction for characterizing the microstructural evolution during annealing.…”
Section: Discussionmentioning
confidence: 98%
“…The cation distribution in the tetrahedral and octahedral sites in partially inverse spinel ferrites can be deduced on the basis of both Rietveld refinement of XRD data and the intensity ratio in the Mössbauer spectra of the sextets due to Fe 3+ cations in the tetrahedral and octahedral sites. Taking into account that combined XRD and Mössbauer spectral studies partially inverse spinel ferrites have concluded that the cation distribution obtained from the X-ray intensity data matches very well with the cation distribution estimated from Mössbauer data, [49][50][51][52] and that the diffraction profile analysis with the Rietveld method allows simultaneously getting the relevant information of the material microstructure, it was selected the use of X ray diffraction for characterizing the microstructural evolution during annealing.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the crystallite sizes of the ZnS nanoparticles increases as its concentration in the nanocomposites increases, which can be signied as the huge nucleation growth of ZnS nanoparticles on the surface of the MnFe 2 O 4 nanoparticles and multiple interfacial strains may also be the possible cause for increasing crystallite sizes of the ZnS nanoparticles. It is well known that Bragg's diffraction peak intensities for (222) and (400) plans are sensitive with the cations in octahedral sites whereas (220) and (422) planes are sensitive to cations in tetrahedral sites 57. The variation of peak intensity (I 220 /I 400 ) for all the samples is tabulated in Table1; it can be speculated that the movement of cations from octahedral to tetrahedral sites increases as the concentration of ZnS increases.…”
mentioning
confidence: 96%
“…The observed values of saturation magnetization, retentivity, and coercivity have suggested the utility of synthesized nanoferrites for electromagnetic applications. The magnetization method as reported by Kumar et al [33] has been utilized to verify the distribution of cations as obtained from X-ray diffraction method. The experimental values of the magneton number have been estimated by employing the following relation [33]:…”
Section: Magnetic Studymentioning
confidence: 99%
“…The theoretical values of the magneton number have been estimated in the light of Neel's two sublattice model [33]:…”
Section: Magnetic Studymentioning
confidence: 99%